2021
DOI: 10.2166/wst.2021.207
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and antibiotic-resistance genes of Pseudomonas spp. and Escherichia coli isolated from untreated hospital wastewater

Abstract: Hospitals are considered an important factor in spread of ARB and ARGs. Purpose of this research was to characterize the microbial populations in hospital wastewater and investigated the prevalence of β-lactamase, SulІ and QnrS resistant genes. In the first step, culture method was used for isolation of Pseudomonas aeruginosa and Escherichia coli. In the next step, accurate identification of isolated bacteria was done with PCR method, then the resistance of the bacteria at different concentrations of antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Thus, hospital wastewaters may represent major sources of pathogenic organisms in public wastewater, playing an important role regarding multidrug-resistant pathogens and also in the propagation of antibiotic resistance in the environment [7]. In fact, many studies have shown that hospital wastewaters contribute to the mobilization and dissemination of important nosocomial pathogens as well as antimicrobial resistance genes and genetic determinants which may reach surface waters, influencing the aquatic ecosystems and interfering with the food chain [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, hospital wastewaters may represent major sources of pathogenic organisms in public wastewater, playing an important role regarding multidrug-resistant pathogens and also in the propagation of antibiotic resistance in the environment [7]. In fact, many studies have shown that hospital wastewaters contribute to the mobilization and dissemination of important nosocomial pathogens as well as antimicrobial resistance genes and genetic determinants which may reach surface waters, influencing the aquatic ecosystems and interfering with the food chain [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient agar (NA) medium was used to cultivate THB and the bacterial count was determined using the plate count method. Primary isolation and identification of Pseudomonas spp ., Acinetobacter spp ., and E. coli were conducted by culturing on Cetrimide agar (CA) and Eosin Methylene Blue agar (EMB), respectively (Baghal Asghari et al, 2021; Banerjee et al, 2017). Different antibiotics in concentrations of 16, 32, 64, and 128 μg/ml were added in culture mediums after autoclaving, and subsequently the medium was distributed on plates.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple dilutions were performed up until a 10 -6 dilution was obtained. Finally, 1 mL of the 10 -6 dilution was inoculated onto Eosin Methylene Blue (EMB, Oxoid) agar medium, followed by incubation for 24 hours at 37°C (Asghari et al 2021).…”
Section: Isolation Characterization and Quantification Of E Colimentioning
confidence: 99%